2012
DOI: 10.3109/0886022x.2012.718953
|View full text |Cite
|
Sign up to set email alerts
|

Nephrotic Syndrome and Acute Tubular Necrosis Due to Meloxicam Use

Abstract: Non-steroidal anti-inflammatory drugs (NSAIDs) are widely used by patients all over the world. Five to eighteen percent of the patients who receive NSAIDs can suffer from kidney-related side effects. Among them, the most relevant are sodium and water retention, hyponatremia, worsening of hypertension or preexisting cardiac failure, hyperkalemia, acute kidney injury, chronic kidney disease, papillary necrosis, nephrotic syndrome (NS), and acute interstitial nephritis. We report the case of a 65-year-old woman w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
8
0
2

Year Published

2012
2012
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 17 publications
1
8
0
2
Order By: Relevance
“…Our findings confirmed previous studies. Case reports and case series showed that NSAID-associated nephrotic syndrome occurs from the exposure duration of ,1 week (30,31) to years (17,32,33). Even further, nephrotic syndrome might develop 6 months after the discontinuation of an NSAID (34).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our findings confirmed previous studies. Case reports and case series showed that NSAID-associated nephrotic syndrome occurs from the exposure duration of ,1 week (30,31) to years (17,32,33). Even further, nephrotic syndrome might develop 6 months after the discontinuation of an NSAID (34).…”
Section: Discussionmentioning
confidence: 99%
“…As a chemical mediator, PGs are essential for kidney hemodynamic including glomerular filtration. In nephrotic syndrome, glomeruli are impaired by the inflammation processes that allow proteins to pass through kidney cell membranes (30,36,37). Hypersensitivity mechanisms of NSAIDs for nephrotic syndrome are caused allegedly by the shift of PG synthesis from COX to lipoxygenase paths, or the release of lymphokines that increase the production of leukotrienes.…”
Section: Discussionmentioning
confidence: 99%
“…NSAIDs as a class (in particular propionic acid derivatives such as fenoprofen) (Table 1), including COX-2 selective drugs, can induce both AIN and a nephrotic syndrome associated with minimal change or membranous nephropathy. 52,53 A 30% rise of NSAID-mediated AIN cases is reported especially in elderly people, mainly because of polypharmacy. Nephrotic syndrome can occur in NSAID-mediated AIN but is rare (less than 1%).…”
Section: Acute and Chronic Renal Damage By Non-selective And Cox-2 Sementioning
confidence: 99%
“…These changes were in the form of fusion of foot processes with focal obliteration of filtration slits resulting in massive proteinuria and hence hyaline casts were found in the renal tubules [2,11,15]. Jorge Vega et al, demonstrated that meloxicam causes tubulo-interstitial nephritis associated with proteinuria manifested histologically in the form of hyaline casts [16].…”
Section: Represent Effect Of Meloxicam On Blood Parameters Of Mice Inmentioning
confidence: 99%